PENGARUH MIKORIZA, MEDIA TANAM DAN FASE TRANSPLANT TERHADAP PERTUMBUHAN BIBIT JELUTUNG (Dyera costulata (Miq.) Hook.f) - Utami, Ning Wikan; Widjaja, E. A. (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
Dyera costulata, usually called as jelutung is belonging into Apocynaceae family.This plant is a potential plant species that has good prospect, especially for timberand latex production. However the seedling grows slowly. The experiment wascarried out in greenhouse, Treub Laboratory, Botani Division, Centre Research forBiology-LIPI, Bogor, using a Factorial Completely Randomized Design with treemain factors in five replications. The first factor is phase of transplant i.e. seedlingwith closed cotyledon, seedling with opened cotyledon, seedling with two firstleaves. The second factor is growth medias i.e. soil, soil+compost (1:1), soil+huskof rice (1:1), soil+compost+ soil+husk of rice (1:1:1), compost+ soil+husk of rice(1:1). The third factor is mycorrhiza i.e. 0, 2, 4 and 6 g/pot The result showed thatthe transplant phase had significant effect on the seedling growth. The best oftransplant phase is seedling with two leaves which has 100% survival, seedlingheight 8.57 cm and number of leaves 5.07 . Mycorrhiza treatment no significanteffect on the seedling growth until 5 months after planting. Growth medias hadsignificant effect at number of leaves. Therefore it is recommended the best mediafor seedling growth are are of soil+ soil+husk of rice (1:1) , or soil+compost + huskof rice = 1:1:1. There was no interaction effect of transplant phase, mycorrhizaand growth media.